2015
DOI: 10.1177/230949901502300323
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Survival and Tumour Characteristics in Patients with Chondrosarcoma

Abstract: The survival rate was lower in patients with higher Evan grading, metastasis, or local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Similarly, p73 expression was found to be an early event in human oral carcinogenesis, and patients with epithelial dysplasia positive for p73 had malignant transformation and developed squamous cell carcinoma by their 2-year follow-up (27). In agreement with these reports, our data showed a correlation between p73 methylation and CS histological grade, which is classified based on cellularity, atypia, and pleomorphism (28,29). In particular, there was significantly lower p73 methylation in grade 1 CS compared to that of grade 2 and grade 3, thereby indicating an association between CS transformation/differentiation and p73 methylationregulated protein expression.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, p73 expression was found to be an early event in human oral carcinogenesis, and patients with epithelial dysplasia positive for p73 had malignant transformation and developed squamous cell carcinoma by their 2-year follow-up (27). In agreement with these reports, our data showed a correlation between p73 methylation and CS histological grade, which is classified based on cellularity, atypia, and pleomorphism (28,29). In particular, there was significantly lower p73 methylation in grade 1 CS compared to that of grade 2 and grade 3, thereby indicating an association between CS transformation/differentiation and p73 methylationregulated protein expression.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies reported that the tumor size was associated with better survival of chondrosarcoma patients 21, 27. Kamal et al 7 found that tumor size was not correlated with survival and Bindiganavile et al 22 revealed that tumor volume (in mL) was not a predictor in chondrosarcoma. In our cohort, tumor size > 10 cm was an independent predictor of both OS and CSS.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate for chondrosarcoma is 75.2%, which is much higher than that of osteosarcoma and Ewing sarcoma 3. Tumor size, grade, stage, local recurrence, metastasis at presentation, systemic treatment, and radiotherapy are all associated with the prognosis of chondrosarcoma 4-7. Patients with chondrosarcoma and metastasis often have a poor prognosis 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature, proton therapy could have been a primary option, but the patient refused to move far away from his residency. CS are still considered fairly radioresistant tumors and, according to literature, CS require doses greater than 60 Gy to achieve local control after incomplete resection [ 6 ]. Even if hypofractionated, RT is not the standard in HN district, we chose a hypofractionated schedule to obtain a higher EQD2 taking into account the biological resistance of CS; moreover, a slight hypofractionation was reported also by other authors in the literature [ 3 ].…”
Section: Discussionmentioning
confidence: 99%